NEGARA, MASYARAKAT SIPIL DAN AGENSI DALAM RELASI ANTARKOMUNAL ISLAM - Nawari Ismail (Harmoni, 2014)
This study is a comparative study that uses qualitative methods. Case selection was based on the following criteria: (1) an area with a plural society and with Special Islamic Splinter Groups (KISK ) and non - KISK, yet was without violent intergroup conflict. The City of Yogyakarta (Ahmadiyah case) and Gowa (An-Nadzir case) was chosen for the first set of cases. (2) An area with a plural society, with KISK members and other Islamic groups, that violent conflict. The second set of cases are thus Kuningan Regency, West Java (Ahmadiyah case) and Sampang Regency, East Java (Shia case). This study uses the purposive method and involves the study of the Executive Board and members of KISK, heads of civic groups such as Islamic organizations (e.g. Local boards of Indonesian Ulama Council), consul agencies related to intercommunal relations, and local government officers. Data was collected through in-depth interviews, discussions, documentaries, and observations, as well as internet sources or websites.